Transition metal complexes bearing a 2,2-bis(3,5-dimethylpyrazol-1-yl) propionate ligand: One methyl more matters - Türkoglu, Gazi; Heinemann, Frank Wilhelm; Burzlaff, Nicolai (Dalton Transactions, 2011)
The new N,N,O ligand 2,2-bis(3,5-dimethylpyrazol-1-yl)propionic acid (2,2-Hbdmpzp) (2) and its transition metal complexes [Mn(2,2-bdmpzp)(CO) ] (3), [Re(2,2-bdmpzp)(CO) ] (4), [Cu(2,2-bdmpzp) ] (5), and [Ru(2,2-bdmpzp)Cl(L)(PPh )] [L = PPh (6), N (7), CO (8a/b), SO (9a/b)] have been synthesized, characterized and compared to analogous complexes bearing a bis(3,5-dimethylpyrazol-1-yl)acetic acid. It was found that the additional methyl group has a remarkable influence on the stability and reactivity of transition metal complexes. © 2011 The Royal Society of Chemistry.